Tourism Development in Lubuk Resam Village, North Seluma Sub-District, Seluma Regency - Ihsan, Alhapis; Saputra, Harius Eko; Imanda, Antonio (Social Sciences Journal, 2025)
. This study investigates the development of tourism in Lubuk Resam Village, located in the North Seluma Sub-District of Seluma Regency. The research applies a qualitative descriptive method to analyze the village's tourism potential using the framework proposed by Buhalis (2000), which includes attractions, accessibility, amenities, and ancillary services. Data were collected through semi-structured interviews and documentation, involving three key informants and two supporting informants from local stakeholders. The findings reveal that Lubuk Resam possesses a variety of natural attractions—such as hot springs, waterfalls, and unique cave formations—that serve as primary tourist magnets. However, access remains a significant challenge due to inadequate road infrastructure, particularly for four-wheeled vehicles. Amenities and supporting facilities, including accommodation, restrooms, and parking areas, are still underdeveloped due to limited village funding. The study suggests that maximizing tourism development in Lubuk Resam requires stronger involvement from external stakeholders, such as regional government bodies and private investors. Their participation is vital for improving infrastructure, enhancing visitor experience, and ensuring sustainability. Furthermore, community engagement must be encouraged to preserve cultural identity while promoting tourism. The study concludes that with strategic planning and cross-sector collaboration, Lubuk Resam has the potential to emerge as a leading tourism village in Bengkulu Province.